Ceramic processing and sintering - Rahaman, M. N. (Materials engineering, 1995)
This work provides a through overview of all relevant issues concerning the processing and sintering of advanced ceramic materials. It discusses powder preparation and characterization; colloidal and sol-gel techniques; powder consolidation and forming; sintering theory and practice; and microstructure evolution. The importance of each step, and the critical interconnections among steps in the overall fabrication of ceramics, are delineated. College or university bookstores may order five or more copies at a special student price, which is available from Marcel Dekker, Inc, on request.